Identifying greener solvents for square wave voltammetry applications in functional food analysis - Montney, Jaycie M.; Siddiqui, Abdur-Rahman; Flores, Sebastian A.; Fhaner, Matthew J. (Frontiers in Environmental Chemistry, 2023)
Electrochemical methods, specifically square wave voltammetry (SWV) offer fast, portable, and quantitative screening for antioxidant levels and lipid degradation in consumer products. Initial studies within our research group utilized benzene as the non-polar component in solvent systems utilized for analysis. In order to explore additional applications of SWV, less hazardous solvent systems that maintain or improve on previous figures of merit for analytes of interest are necessary. To this extent, ethanol was selected as the polar solvent under the 7 th principle of green chemistry (use of renewable feedstocks). To replace our non-polar species (benzene), four solvent candidates were identified under the 5 th principle of green chemistry (safer solvents and auxiliaries) including diethyl ether, acetonitrile, isopropyl alcohol, and ethyl acetate. Each solvent was investigated on its own, and then in varying combinations of v/v ratios with ethanol. Each solvent combination was used to investigate the limit of detection, lower limit of quantitation, sensitivity, and linearity of previously studied antioxidants butylated hydroxytoluene, sesamol, and rosemary extract. Each antioxidant was found to yield improved figures of merit depending on the solvent combination tested. After comparing all antioxidant figures of merit, it was found that 50%-50% ethanolacetonitrile and 50% -50% ethanolethyl acetate were within the top five solvent systems for all antioxidants tested, providing a more green alternative to benzene solvent systems.